PERHITUNGAN BEBAN PENDINGIN PADA COLD ROOM DAN ABF-1 UNTUK PENYIMPANAN PRODUK HASIL LAUT DI PT. MINA USAHA HARAPAN - Kakiay, Isaac Bryant; Waas, Kristofol; Lekatompessy, Roy R. (Journal Mechanical Engineering, 2024)
Refrigeration has become an essential part in the design of spaces that will be occupied by people or products intended to provide space temperature, humidity, other process requirements. Refrigeration was originally used to produce ice, as technology advances, refrigeration has an important role in commercial and non-commercial refrigeration. Research on efficient refrigeration has been carried out by several previous studies. Previous methods were used by calculating cooling efficiency and heat loads that affect cold storage cooling.Based on an interview with one fishery company focused on processing quality seafood products located in PPN Tantui, PT Mina Usaha Harapan, the energy consumption for the cooling system takes up almost 70%-80% of the total energy expenditure of the company. Due to several factors, including excessive heat loads provision, or inefficient cold storage design. Therefore, author wants to calculate the cold storage performance in one of the seafood processing companies based on eco-fishing located in PPN Tantui, PT Mina Usaha Harapan.Calculations and analysis have been carried out in the previous chapter, several conclusions is made: 1) The average value of evaporator capacity is 34.96 kW for Cold Room and 57.39 kW for Air Blast Freezer 2) The calculated total load value (without product load) is 11.94 kW for Cold Room and 3.56 kW for ABF. 3) The company set a time of 9 hours to freeze 3500 kg of seafood, but according to calculation results, it only takes 7 hours to freeze 3830.4 kg of products with product temperature reaching -21 Í¦C.Keywords: vapor compression cold storage, refrigeration load, cold room, abf, cold storage, evaporator capacity, seafood products